The Theory of Moral sentiments and the Wealth of Nations. Ethics, Jurisprudence and Political Economy throughout the intellectual history of Adam Smith - Piqué, María del Pilar (2019)
This paper aims to address two research questions that have not been sufficiently examined by specialized studies of the intellectual history of Adam Smith. The first question asks why Smith, after developing his theory of sympathy in the first editions of The Theory of Moral Sentiments, started working on a theory of jurisprudence and ended up writing The Wealth of Nations. The second question asks why Smith, after writing and republishing The Wealth of Nations, asserted that he could not complete his theory of jurisprudence and incorporated a new part dedicated to virtue ethics in the last edition of The Theory of Moral Sentiments in 1790. The paper shows that: 1) after developing his theory of sympathy in the first edition of The Theory of Moral Sentiments, Smith stated that a theory of jurisprudence was necessary to form rules of justice that guarantee social order, and in the search for that theory he ended up writing The Wealth of Nations; 2) in The Wealth of Nations, Adam Smith was devoted to studying the development of commerce in modern society and the conduct of the mercantile individual who pursued his own interest, and was incapable of elaborating on those general principles of justice that would ensure social harmony. Smith then delved into virtue ethics in order to recommend virtuous conduct that encourages mercantile individuals to become good citizens. The paper concludes by contending that economics would benefit from a better understanding of the relationship between political economy, jurisprudence and ethics in the work of Adam Smith. Specifically, economics would broaden in scope of study and contribute to larger debates about the past, present and future of modern civilization.